RNA sequencing of the nephron transcriptome: a technical note - Jae Wook Lee (The Korean Society of Nephrology, 2015)
To understand the functions of the kidney, the transcriptome of each part of the nephron needs to be profiled using a highly sensitive and unbiased tool. RNA sequencing (RNA-seq) has revolutionized transcriptomic research, enabling researchers to define transcription activity and functions of genomic elements with unprecedented sensitivity and precision. Recently, RNA-seq for polyadenylated messenger RNAs [poly(A)'-mRNAs] and classical microdissection were successfully combined to investigate the transcriptome of glomeruli and 14 different renal tubule segments. A rat kidney is perfused with and incubated in collagenase solution, and the digested kidney was manually dissected under a stereomicroscope. Individual glomeruli and renal tubule segments are identified by their anatomical and morphological characteristics and collected in phosphate-buffered saline. Poly(A)'-tailed mRNAs are released from cell lysate, captured by oligo-dT primers, and made into complementary DNAs (cDNAs) using a highly sensitive reverse transcription method. These cDNAs are sheared by sonication and prepared into adapter-ligated cDNA libraries for Illumina sequencing. Nucleotide sequences reported from the sequencing reaction are mapped to the rat reference genome for gene expression analysis. These RNA-seq transcriptomic data were highly consistent with prior knowledge of gene expression along the nephron. The gene expression data obtained in this work are available as a public Web page (https://helixweb.nih.gov/ESBL/Database/NephronRNAseq/) and can be used to explore the transcriptomic landscape of the nephron.